Factors influence depositors’ withdrawal behavior in Islamic banks: a theory of reasoned action - Abduh, Muhamad; Duasa, Jarita; Omar, Mohd. Azmi (World Academy of Science, Engineering and Technology (W A S E T), 2011)
Unlike its conventional counterpart, Islamic principles forbid Islamic banks to take any interest-related income and thus makes deposits from depositors as an important source of fund for its operational and financing. Consequently, the risk of deposit withdrawal by depositors is an important aspect that should be well managed in Islamic banking. This paper aims to investigate factors that influence depositors’ withdrawal behavior in Islamic banks, particularly in Malaysia, using the framework of theory of reasoned action. A total of 368 respondents from Klang valley are involved in the analysis. The paper finds that all the constructs variable i.e. normative beliefs, subjective norms, behavioral beliefs, and attitude towards behavior are perceived to be distinct by the respondents. In addition, the structural equation model is able to verify the structural relationships between subjective norms, attitude towards behavior and behavioral intention. Subjective norms gives more influence to depositors’ decision on deposit withdrawal compared to attitude towards behavior.